Evaluasi Tingkat Keberhasilan Aplikasi Tije Menggunakan Metode Pieces Framework - Ramanda, Kresna; Abadi, Muhamad Sahrul (Program Studi Sistem Informasi, Universitas Multi Data Palembang, 2024)
The TIJE application is a digital platform that has been specifically developed to provide smartphone users convenient online access to Transjakarta information. In order to use the platform, individuals must first establish an internet connection and then download the TIJE application. In order to evaluate user satisfaction with the TIJE application, it is essential to identify any faults or problems that may be associated with its utilization. One such way for assessment is the use of the PIECES framework. The study utilizes a quantitative research technique, using a survey administered via Google Forms as the principal instrument for data gathering. The data that has been gathered is then subjected to analysis using the statistical software package SPSS version 26. The assessment of user satisfaction with the TIJE application may be conducted with the PIECES approach. This approach assesses user satisfaction across many areas. The findings suggest that participants assigned a rating of 4.04 to Performance, 4.23 to Information and Data, 4.25 to Economy, 4.51 to Control and Security, 4.55 to Efficiency, and 4.59 to Service. The ratings achieved for the TIJE application vary from 4.2 to 5, indicating a notable degree of customer satisfaction.